IMPUNITY AND DEMOCRATIC QUALITY IN LATIN AMERICA (2015-2021): PATTERNS OF CONVERGENCE AND DIVERGENCE (Journal of International Studies, 2025)
In 2019, a wave of protests broke out in many countries in the Latin American region. It started in Chile and spread to Bolivia, Ecuador, and Colombia. In 2020, it spread to more countries in the region: Argentina, Brazil, Panama, Honduras, and Peru. Even today, outbreaks of violence can still be observed across the region. Although they have different origins and consequences, common elements can be observed. The origins of the problem can be traced back to the linkage between two variables: one related to the malfunctioning of the region's justice systems as reflected in the levels of impunity. The other factor is the quality of Latin American democracies. The aim of this piece of work is to explore the possible relation between those two factors for Latin-American countries between 2015 and 2021. To do this, certain variables of both aspects are studied through Pearson’s Correlations. The result of the statistical analysis is shown and discussed in the main part of the paper. Finally, some ways of action are proposed to try and give a possible solution to this problem.